Public spending mechanisms and gross domestic product (GDP) growth in the agricultural sector (1970–2016): Lessons for Nigeria from agricultural policy progressions in China - Apata, Temidayo Gabriel (Bulletin of Geography. Socio-economic Series, 2019)
China has pursued a sustainable path of development in line with reality for four decades. Economic restructuring started in its vast rural areas, focusing on reforms targeting income increase for rural farmers. These radical sustainable policies that China’s political leaders imbibed were not embraced by Nigeria's past leaders and these resulted in the bane of underdevelopment. The study examines the level and composition of the drivers of public-spending policy mechanisms that contribute to gross domestic product (GDP) growth in the agricultural sector in China and Nigeria and draws up a model of Chinese development for Nigeria. Secondary data was used and were sourced from FAOSTAT and International Monetary Fund's Government-Finance Statistics (various issues) from 1970–2016. Random-effects model results revealed that the policy of public-expenditure (PUEXP) and intervention (INTEV) variables were significant but negative, while enterprise-development (ENTDEV), drivers of development (DRIVERS) and Dummy D1t (modest public-expenditure access) were significant and positive for Nigeria. Three variables were significant and positive. The dummies D1t and D2t (macro-economic stability) were positive and significant for China. Public-expenditure and GDP growth has an inverse relationship in Nigeria, but a direct relationship in China. In Nigeria, PUEXP coefficient is ˗0.6810 and 0.8902 for China. Hence, macro-economic stability, enhanced market mechanisms and economic progress resulted in China and hereby lessons are drawn for Nigeria. Public leaders are responsible for governing the market in a manner that induces businesses to produce public value. However, if public-policy mechanisms are not well-designed to fit the economy's needs it could significantly influence the economy in a negative way, and the society bears the costs.